Integrated Educational Entrepreneurship and Institutional Sustainability in Pesantren: Reframing Drucker’s Innovation Theory - Vikri Natasya Ayu Kusuma; Soyfan Tsauri; Imron Fauzi (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
This study examines how integrated educational entrepreneurship contributes to institutional sustainability in pesantren by reframing Peter F. Drucker’s innovation theory within the context of Islamic educational institutions. The study aims to analyze how entrepreneurial innovation, opportunity recognition, and institutional governance are integrated to support infrastructure sustainability, vocational education, and organizational resilience in pesantren. This research employed a qualitative embedded case study approach conducted at a pesantren-based vocational institution in Indonesia. Data were collected through in-depth interviews, non-participant observations, and documentation with 12 informants, including school leaders, pesantren caregivers, business unit managers, teachers, alums, and supporting stakeholders. Data were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña combined with the Gioia approach to identify first-order concepts, second-order themes, and aggregate dimensions. The findings reveal that entrepreneurial activities within pesantren function not merely as income-generating programs but also as integrated institutional mechanisms that simultaneously support infrastructure development, vocational learning, organizational resilience, and financial self-reliance. Entrepreneurial innovation emerged through organizational failure, financial limitations, market adaptation, digital transformation, and collective institutional learning. The study also identified a cyclical reinvestment mechanism in which entrepreneurial profits are systematically reinvested into new infrastructure and educational business sectors. The novelty of this study lies in the conceptualization of integrated educational entrepreneurship, in which entrepreneurship functions simultaneously as a pedagogical process, a sustainability mechanism, and an institutional governance strategy. This study contributes theoretically by extending Drucker’s innovation theory beyond market-oriented entrepreneurship and contributes practically by offering an alternative model for sustainable infrastructure financing in Islamic educational institutions.